A new record and a new ichnospecies of Arachnostega from the Middle Miocene of Egypt. Issue 6 (December 2018) - Vinn, Olev; El-Sabbagh, Ahmed M.; El-Hedeny, Magdy M.; Rashwan, Mohamed A.; Al Farraj, Saleh A.
Abstract: The ichnogenus Arachnostega Bertling, 1992 is recorded for the first time from a bioeroded, coral-rich, Middle Miocene limestone bed in the middle Siwa Escarpment Member (Marmarica Formation) at Siwa Oasis, northern Western Desert of Egypt. These burrowing traces are preserved on the surface of a few internal moulds of bivalves and gastropods. Until now, the ichnogenus Arachnostega included a single ichnospecies, A. gastrochaenae Bertling, 1992. In the material studied herein, two ichnospecies are identified, described, illustrated and compared with other, similar traces. One of these is a new ichnospecies of Arachnostega ; this is here named A. siwaensis ichnosp. nov. It is distinguished from A. gastrochaenae in the possession of tunnels that usually branch in a V-pattern; intervals of ramification are longest in the main branch and decrease in second- and third-order branches. Arachnostega traces were produced in a warm, low-energy, shallow-marine (<10 m water depth) environment. Polychaetes are the most likely producers of marine Arachnostega, which are commonly occurred in the same studied bed. This new occurrence is significant in extending the known stratigraphical and geographical ranges of Arachnostega into the Middle Miocene of Egypt.